BUDAYA KERJA PERANGKAT KAMPUNG TUALANG DALAM MENINGKATKAN PELAYANAN PUBLIK DI KANTOR PENGHULU KAMPUNG TUALANG TAHUN 2023 - Arumningtias, Sekar; ,, Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The phenomenon of the work culture of the Tualang Village apparatus at the Tualang Village Headman's Office has not been fully implemented. The current work culture still faces various obstacles, especially in the field of government. These obstacles hinder the formation of a disciplined, professional, and service-oriented work culture. As a result, the work culture of the apparatus is not optimal and services to the community are less than optimal. This condition shows that work culture is one of the main factors influencing public services. Therefore, the formation of a good work culture is very important in the work environment, because the community places great hopes and trust in the government in providing public services. This study aims to determine the work culture and factors that influence the work culture in improving public services at the Tualang Village Headman's Office using the work culture theory according to Taliziduhu Ndraha. The research method used is a descriptive qualitative method. The type of research data is primary data obtained from interviews with research informants and secondary data obtained from documents related to the research topic. Data collection techniques through interviews and documentation. The results of the study indicate that the work culture of village officials seen from the habit of carrying out main tasks and functions and discipline is not yet effective because there are still differences between the behavior of village officials in carrying out their responsibilities. Regulations that are not yet consistent and sanctions are still found so that discipline and professionalism have not been optimally formed. Cultural values and organizational values in Tualang Village support each other in creating an ethical, productive, and sustainable government by maintaining a balance between tradition and modernity. Several factors that influence the less than optimal work culture of Tualang Village officials include discipline factors, education and training factors and facilities and infrastructure factors. Keywords: Work culture, Village apparatus, and Public services.